The Use of Herringbone technique in Comprehending Recount Text at The Tenth Grade Students of Madrasah Aliyah Swasta Terpadu Duri - deny silvia (STAI Hubbulwathan Duri, 2017)
This study was conducted to find out whether there was a significant difference between reading comprehension recount text ability of students who were taught by using Herringbone technique and those who were taught without using Herringbone technique. The research method used was experimental research. The instruments for collecting data was test. It was given to subjects before and after the experiment. The test was used in order to find out the students comprehension ability on recount text. The subject chosen for this study were 62 students at the tenth grade of Madrasah Aliyah Swasta Terpadu Duri. They were divided into two group: experimental and control group.Based on finding, the results of t-test and interpretations, the following conclusions were drawn: (1) Herringbone Technique was applicable to improve students` ablity in comprehending recount text, (2) there was a significant difference between reading comprehension ability of students who were taught before using Herringbone Technique and those who were taught after using Herringbone Technique. And (3) there was significant effect of using Herringbone Technique in comprehending recount text at the Tenth Grade Students of Madrasah Aliyah Swasta Terpadu Duri. It was evidence by calculation of t- test. The result of t-test was (2, 00 7, 15 2, 65). It could be concluded that Ha was accepted. Key Words: Herringbone Technique, Recount Text